Design and test of digital circuits by quantum-dot cellular automata - Huang, Jing, 1970-; Lombardi, Fabrizio, 1955- (Artech House, 2008)
The first book devoted to this emerging nanoscale technology, being viewed by most experts as a superior alternative to traditional CMOS circuit technology. QCA (Quantum-dot Cellular Automata) provides nanoscale solutions that overcome the physical limitations of CMOS technology used in computing and.